Risk Factors for Deterioration of the Clinical Condition of Cull Dairy Cows During Transport to Slaughter - Dahl-Pedersen, Kirstin; Herskin, Mette S.; Houe, Hans; Thomsen, Peter T. (Frontiers in Veterinary Science, 2018)
Cull dairy cows are typically transported to slaughter by road. Across different types of cattle, road transport is recognized as stressful. Cull dairy cows may have different injuries or weaknesses and may thus be more vulnerable to transport stress than other types of cattle. The aim of this study was to investigate whether the clinical condition of cull dairy cows deteriorates during transport (<8 hours), and to evaluate risk factors for potential deterioration of the clinical condition. A total of 411 dairy cows were clinically examined on farm before loading and again after unloading at the slaughter plant. The clinical examination included locomotion, presence of wounds, milk leakage and general condition. One fifth of the cows either became lame or more lame during transport, and there was a significant increase in the proportion of lame cows after transport (41% after vs. 31% before, P<0.0001). A significant increase in the proportion of cows with milk leakage (17% vs. 1%, P<0.0001) and wounds (34% after vs. 22% before, P<0.0001) after transport were also found. Low body condition score (BCS) (<2.75) (P=0.001), early or late lactation (<100 days in milk (DIM) or >300 DIM) (P=0.01), digital dermatitis inat the hind feet (P=0.01) and pelvic asymmetry (P=0.001) were identified as risk factors for the deterioration in lameness during transport. Early lactation (<100 DIM) (P=0.04) and transport distance (>100 km) (P=0.006) were identified as risk factors for milk leakage. For wounds, no significant risk factors were found. The results demonstrate that cull dairy cows are vulnerable to the strains of transport, even journeys shorter than 8 hours, to the extent that the occurrence of clinical findings were increased after transport in cows legally considered fit for transport. These results call for further research into the animal welfare implications and optimization of cattle transport.